2016
DOI: 10.1007/s00702-016-1521-x
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged striatal volume in adults with ADHD carrying the 9-6 haplotype of the dopamine transporter gene DAT1

Abstract: The dopamine transporter gene, DAT1 (SLC6A3), has been studied extensively as a candidate gene for attention-deficit/hyperactivity disorder (ADHD). Different alleles of variable number of tandem repeats (VNTRs) in this gene have been associated with childhood ADHD (10/10 genotype and haplotype 10-6) and adult ADHD (haplotype 9-6). This suggests a differential association depending on age, and a role of DAT1 in modulating the ADHD phenotype over the lifespan. The DAT1 gene may mediate susceptibility to ADHD thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
0
16
1
2
Order By: Relevance
“…There is some evidence that cortical thickness is a better trait for capturing the heritability of the brain's morphology . In children and adolescents with ADHD, thickness of the lateral prefrontal cortex and the cingulated cortex was increased in 98 cases with the 10R‐allele . Interestingly, homozygotes for the SLC6 A3 10R allele showed increased thickness in the right cingulated gyrus, but decreased cortical thickness in the lateral prefrontal cortex.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that cortical thickness is a better trait for capturing the heritability of the brain's morphology . In children and adolescents with ADHD, thickness of the lateral prefrontal cortex and the cingulated cortex was increased in 98 cases with the 10R‐allele . Interestingly, homozygotes for the SLC6 A3 10R allele showed increased thickness in the right cingulated gyrus, but decreased cortical thickness in the lateral prefrontal cortex.…”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
“…As studies most often use younger aged samples, it is nevertheless interesting to consider whether imaging genetics effects persist into adulthood or whether they change as a function of brain maturation, medication, or further psychiatric comorbidity. In a cross‐sectional structural magnetic resonance imaging (sMRI) study with childhood/adolescent ADHD, an adult ADHD case–control sample, and an adult population‐based sample, only the adult ADHD risk haplotype 9‐6 of SLC6A3 had a 5.9% larger striatum volume . While there are not yet studies sufficiently powered to look at the longitudinal course of striatal volume as a function of an interaction between medication and genotype, a recent study in an adolescent cohort revealed that the left striatal volume was reduced in participants with ADHD carrying one SLC6A3 10‐6 haplotype independent of medication status …”
Section: Molecular Genetic Studiesmentioning
confidence: 99%
“…A total of 76 records were retrieved for the ADHD search term, and a total of 16 research articles describing case-control studies were eligible for review according to our criteria. To those, we added three more recent papers from our own group ([Onnink et al, 2016;Sokolova et al, 2015;van der Meer et al, 2015]; Figure 1). Most of the studies investigated a single gene (all in Caucasians), and three studies investigated multiple genes (2 in Caucasians, 1 in Asians).…”
Section: Imaging Genetics Of Adhd Candidate Genesmentioning
confidence: 99%
“…(MADRAS et al, 2005;FRANKE et al, 2012). Além disso, a presença do haplótipo 9-6 já tem sido associada ao aumento no volume estriatal em indivíduos com TDAH (ONNINK et al, 2016).…”
Section: Etiologia Do Tdahunclassified
“…O estriado tem participação na hiperatividade (FULTON, 1951;KELLY;MOORE, 1976;YOSHIDA et al, 1991) e pode ser divido em duas regiões, o núcleo caudado e o putâmen. Apesar de já se ter observado aumento da região pré-frontal e maior volume do núcleo caudado em indivíduos com TDAH (SEMRUD-CLIKEMAN et al, 2014;ONNINK et al, 2016), a maior parte dos estudos apontam diminuição dessa região (CASTELANOS et al, 1996;FILIPEK et al, 1997;HILL et al, 2003), e provavelmente isso se deve às diferentes metodologias empregas para quantificar os desvios volumétricos (IANNACCONE et al, 2015). Além destas diferenças anatômicas, disfunções no funcionamento do DAT estão envolvidas na hiperatividade (SPENCER et al, 2005;MADRAS et al, 2005).…”
Section: Neurobiologia Do Tdah: Aspectos Atencionais E Hiperatividadeunclassified